Dogs with acute myeloid leukemia or lymphoid neoplasms (large cell lymphoma or acute lymphoblastic leukemia) may have indistinguishable mediastinal masses on radiographs. Issue 5 (3rd May 2018) - Epperly, Erin; Hume, Kelly R.; Moirano, Steven; Stokol, Tracy; Intile, Joanne; Erb, Hollis N.; Scrivani, Peter V.
Abstract: Acute myeloid leukemia is an uncommon hematopoietic neoplasm of dogs that should be differentiated from lymphoid neoplasms, such as lymphoma, because of different treatment protocols and a worse prognosis. Thoracic radiography is performed frequently in dogs with suspected hematopoietic neoplasia, and detecting a mediastinal mass often prioritizes lymphoma as the most likely diagnosis. However, we have observed a mediastinal mass in several dogs with acute myeloid leukemia and hypothesized that (1) the frequency of a mediastinal mass was higher and (2) the size of the mass was larger in dogs with acute myeloid leukemia compared to dogs with lymphoid neoplasms. In this analytical study (observational, retrospective, and cross‐sectional), the sample population included 238 dogs with hematopoietic neoplasia. These dogs were divided into lymphoid (large cell lymphoma, acute lymphoblastic leukemia) and myeloid groups based on standard phenotyping tests. A mediastinal mass was detected during thoracic radiography in 73/218 (33%) and nine of 20 (45%) dogs in the lymphoid and myeloid groups ( P  = 0.21), respectively. The median size ratio of mediastinal mass to cardiac silhouette was 0.20 and 0.23 in the lymphoid and myeloid groups ( P  = 0.96), respectively. Additionally, we observed normal thoracic radiographs in 111/218 (51%) dogs in the lymphoid group and nine of 20 (45%) dogs in the myeloid group. In conclusion, acute myeloid leukemia should be considered when a mediastinal mass is detected during radiography in dogs with suspected hematopoietic neoplasia—but the presence or size of a mediastinal mass does not differentiate between myeloid and lymphoid neoplasms.